The effects of negative emotions on sensory perception: fear but not anger decreases tactile sensitivity - Kelley, Nicholas J.; Schmeichel, Brandon J. (Frontiers in Psychology, 2014)
Emotions and sensory perceptions are closely intertwined. Of the five senses sight has been by far the most extensively studied sense in emotion research. Relatively less is known about how emotions influence the other four senses. Touch is essential for nonverbal communication in both humans and other animals. The current investigation tested competing hypotheses about the effect of fear on tactile perception. One hypothesis based on evolutionary considerations predicts that fear enhances sensory perception, including tactile sensitivity. A competing hypothesis based on research on peripheral psychophysiology predicts that fear should decrease tactile sensitivity. Two experiments that induced negative emotional states and measured two-point discrimination ability found that fear reduces tactile sensitivity relative to anger or a neutral control condition (Studies 1 and 2). These findings did not appear to be driven by participants’ naïve beliefs about the influence of emotions on touch (Study 3). The results represent the first evidence of the causal impact of emotional states on tactile sensitivity, are consistent with prior evidence for the peripheral physiological effects of fear, and offer novel empirical grounds for developing and advancing theories of emotional influences on sensory perception.